Effect of the portland-limestone cement grades on the compressive strength of hollow sandcrete blocks (2014)
The commercial sandcrete block makers in Nigeria use the same cement-sand mix ratio for sandcrete blocks production irrespective of the cement grade. Investigation revealed that the compressive strengths of hollow sandcrete blocks produced with Portland-limestone cement grade 42.5 are higher than the sandcrete blocks produced with cement grade 32.5. The use of stronger sandcrete blocks produced with cement grade 42.5 will ensure the construction of stronger buildings and other sandcrete blocks-based infrastructures and reduce the incessant failure of building and other sandcrete blocks-based infrastructures in Nigeria at no additional cost as both cement grades cost the same amount in Nigeria. It is recommended that the Standards Organisation of Nigeria should create grassroots awareness on the different cement grades in Nigeria and specify that Portland-limestone cement grade 42.5 be used for sandcrete blocks production.